Comparing the Effects of Kamikihito in Japan and Kami‐Guibi‐Tang in Korea on Memory Enhancement: Working Towards the Development of a Global Study. (23rd October 2014) - Watari, Hidetoshi; Shigyo, Michiko; Tanabe, Norio; Tohda, Michihisa; Cho, Ki‐Ho; Kyung, Park Su; Jung, Woo Sang; Shimada, Yutaka; Shibahara, Naotoshi; Kuboyama, Tomoharu; Tohda, Chihiro
<x xml:space="preserve">Abstract</x> Traditional medicine is widely used in East Asia, and studies that demonstrate its usefulness have recently become more common. However, formulation‐based studies are not globally understood because these studies are country‐specific. There are many types of formulations that have been introduced to Japan and Korea from China. Establishing whether a same‐origin formulation has equivalent effects in other countries is important for the development of studies that span multiple countries. The present study compared the effects of same‐origin traditional medicine used in Japan and Korea in an in vivo experiment. We prepared drugs that had the same origin and the same components. The drugs are called kamikihito (KKT) in Japan and kami‐guibi‐tang (KGT) in Korea. KKT (500 mg extract/kg/day) and KGT (500 mg extract/kg/day) were administered to ddY mice, and object recognition and location memory tests were performed. KKT and KGT administration yielded equivalent normal memory enhancement effects. 3D‐HPLC showed similar, but not identical, patterns of the detected compounds between KKT and KGT. This comparative research approach enables future global clinical studies of traditional medicine to be conducted through the use of the formulations prescribed in each country. Copyright © 2014 John Wiley & Sons, Ltd.